2023
DOI: 10.1038/s41467-023-36400-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of phosphatase CTDNEP1 potentiates aggressive medulloblastoma by triggering MYC amplification and genomic instability

Abstract: MYC-driven medulloblastomas are highly aggressive childhood brain tumors, however, the molecular and genetic events triggering MYC amplification and malignant transformation remain elusive. Here we report that mutations in CTDNEP1, a CTD nuclear-envelope-phosphatase, are the most significantly enriched recurrent alterations in MYC-driven medulloblastomas, and define high-risk subsets with poorer prognosis. Ctdnep1 ablation promotes the transformation of murine cerebellar progenitors into Myc-amplified medullob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…CTDNEP1 regulates nuclear membrane amount and lipid composition through activation of the phosphatidic acid phosphatase, lipin1 67,74,83,84,86,90 , which has downstream effects on chromosome segregation, post-mitotic nuclear assembly, nuclear pore insertion, and protein stability 65,67,80,87,91 . CTDNEP1 may also regulate major signaling pathways, including myc, BMP and WNT, that can affect actin organization through lipin-independent mechanisms [92][93][94][95][96][97][98] . Our analysis of nuclear features after CTDNEP1 depletion demonstrates that the increase in membrane rupture is due to a new mechanism not linked to nuclear lamina organization, actin bundle organization, or nuclear pore insertion defects.…”
Section: Discussionmentioning
confidence: 99%
“…CTDNEP1 regulates nuclear membrane amount and lipid composition through activation of the phosphatidic acid phosphatase, lipin1 67,74,83,84,86,90 , which has downstream effects on chromosome segregation, post-mitotic nuclear assembly, nuclear pore insertion, and protein stability 65,67,80,87,91 . CTDNEP1 may also regulate major signaling pathways, including myc, BMP and WNT, that can affect actin organization through lipin-independent mechanisms [92][93][94][95][96][97][98] . Our analysis of nuclear features after CTDNEP1 depletion demonstrates that the increase in membrane rupture is due to a new mechanism not linked to nuclear lamina organization, actin bundle organization, or nuclear pore insertion defects.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the likely possibility that CTDNEP1 can dissociate from NEP1R1 in cells, which has recently been demonstrated 16 . Dissociation from NEP1R1 may be a critical factor in regulating CTDNEP1 function, which could either lead to CTDNEP1 protein degradation 16 , independent functions of CTDNEP1 (e.g dephosphorylation of nuclear myc 20 ), or association with other yet identified regulatory subunits.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the likely possibility that CTDNEP1 can dissociate from NEP1R1 in cells, which has recently been demonstrated 16 . Dissociation from NEP1R1 may be a critical factor in regulating CTDNEP1 function, which could either lead to CTDNEP1 protein degradation 16 , independent functions of CTDNEP1 (e.g dephosphorylation of nuclear myc 20 ), or association with other yet identified regulatory subunits. Future studies addressing these issues may take advantage of the soluble complex we identified that is sufficient for complex formation, and/or the fusion complex of CTDNEP1-NEP1R1 that covalently links the two proteins together and increases thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…The key differences from fungi in the metabolic pathways that control membrane synthesis as well as emerging evidence for a tumor suppressor function of human CTDNEP1 motivate further analysis of the regulation of this pathway in mammalian cells. Loss of function mutations in CTDNEP1 are frequently observed in specific subtypes of medulloblastomas and were recently found to be enriched in medulloblastomas with MYCamplification and genomic instability (Jones et al, 2012;Northcott et al, 2012;Luo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The key differences from fungi in the metabolic pathways that control membrane synthesis as well as emerging evidence for a tumor suppressor function of human CTDNEP1 motivate further analysis of the regulation of this pathway in mammalian cells. Loss of function mutations in CTDNEP1 are frequently observed in specific subtypes of medulloblastomas and were recently found to be enriched in medulloblastomas with MYC-amplification and genomic instability (Jones et al, 2012; Northcott et al, 2012; Luo et al, 2023). We had previously shown that ER expansion interferes with chromosome segregation causing higher rates of micronuclear formation (Merta et al, 2021), suggesting a link between dysregulated lipid synthesis and chromosomal instability in cancer cells.…”
Section: Introductionmentioning
confidence: 99%